Syphilis in Pregnancy: Education to Increase Knowledge in Reproductive Couples - Sulistyowati, Sri; Bachnas, Muhammad Adrianes; Yuliantara, Eric Edwin; Anggraini, Nutria Widya Purna; Respati, Supriyadi Hari; Nurinasari, Hafi; Ridwan, Robert; Astetri, Lini; Nuur, Aliffudin; Pradana, Muhammad Denny Gagah; Khoeronisa, Siti; Rahmawati, Oktantia Dyah (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Syphilis is believed to be one of the oldest diseases, first discovered in the late 15th century. Indonesian Ministry of Health reported a total of 76,923 new cases in 2020. WHO has set an ambitious target to reduce the incidence by 90% before 2030, in spite of slow global response. This number is lower than the number obtained in 2019, which was 4,169 people. Syphilis can be transmitted through sexual contact, blood transfusion, and vertical mother-to-child transmission (MTCT). It is estimated that the risk of transplacental infection ranges from 20-80%, depending on various factors, such as the stage of infection in the mother. This study aimed to assess the effect of counseling in increasing patient knowledge of syphilis cases in pregnancy. Subjects and Method: This was a quasi experiment conducted at obstetrics and gynecology department in Dr. Moewardi Hospital, Surakarta, Central Java, Indonesia, in June 2025. A sample of 84 pregnant women was selected for this study. The independent variable was counselling. The dependent variable was knowledge about Syphilis in pregnancy. Knowledge was tested before and after counselling. The data were examined using independent t test. Results: The knowledge score of pregnant women about syphilis after the intervention (Mean= 77.14; SD= 13.85) was higher than before (Mean= 56.43; SD= 15.88), and it was statistically significant (p <0.001). Conclusion: The results of this study indicate that this recovery is effective in improving understanding of syphilis cases in pregnancy in obgyn polyclinic patients at Dr. Moewardi Hospital.